Liquid metal fiber based on wet spinning and preparation method thereof

CN119877148BActive Publication Date: 2026-10-27DONGHUA UNIV +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510069488.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2026-10-27
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

但其缺点在于:导电粒子只有在达到渗流阈值时才能形成连续的导电路径;拉伸或弯曲可能破坏导电粒子间的接触,导致导电性下降;高填充量的导电粒子虽能提升导电性,但会降低材料的柔性,在多次拉伸循环中,导电网络容易断裂或退化,导致导电性衰减

Benefits of technology

[0060](1)本发明的一种基于湿法纺丝的液态金属纤维,具有优良的拉伸-回复稳定性和拉伸-导电稳定性,该纤维在反复拉伸和松弛过程中能够保持其形状和性能的稳定性,同时导电性不受机械变形的显著影响;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877148B_ABST
    Figure CN119877148B_ABST
Patent Text Reader

Abstract

The application relates to a liquid metal fiber based on a wet spinning method and a preparation method thereof, and specifically relates to a core-sheath structure fiber prepared by adopting a wet spinning process, and a liquid metal fiber obtained after heat preservation and annealing; in the core-sheath fiber, the raw material corresponding to the sheath layer is spinning liquid I, and the raw material corresponding to the core layer is spinning liquid II; the spinning liquid I is prepared by adding a polymer elastomer I into an organic solvent I; the spinning liquid II is prepared by adding a liquid metal, a solid conductive substance and a polymer elastomer II into an organic solvent II; the product liquid metal fiber has a core-sheath structure, the sheath layer is composed of the polymer elastomer I, and the core layer is composed of the liquid metal, the solid conductive substance and the polymer elastomer II. The application realizes high-efficiency compatibility of the liquid metal and the base material through the wet spinning method, has excellent spinnability, can be continuously prepared, and the prepared liquid metal fiber has excellent tensile-recovery stability and tensile-conductive stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of smart clothing technology and relates to a liquid metal fiber based on wet spinning and its preparation method. Background Technology

[0002] With the rapid development of wearable devices, smart clothing, and flexible electronic devices, the demand for conductive fibers that combine conductivity, flexibility, and durability is increasing rapidly. Conductive fibers are key components of these devices, requiring both excellent conductivity and stability under dynamic stress conditions such as tension and bending. Traditional metal wires have good conductivity, but their rigidity and brittleness make them prone to breakage when bent or stretched, making them unsuitable for the needs of flexible electronics.

[0003] Conductive fibers formed by combining conductive particles with flexible polymers possess both flexibility and conductivity. However, they have drawbacks: conductive particles can only form continuous conductive paths when the percolation threshold is reached; stretching or bending may disrupt the contact between conductive particles, leading to a decrease in conductivity; while high-filling-content conductive particles can improve conductivity, they reduce the flexibility of the material, and the conductive network is prone to breakage or degradation during repeated stretching cycles, resulting in conductivity decay.

[0004] Liquid metals are materials with unique physical and chemical properties, generally referring to metals or metal alloys that are liquid at or near room temperature, such as gallium-based, indium-based, and tin-based alloys. Due to their low melting point, high electrical and thermal conductivity, and good fluidity, liquid metals have broad application prospects in flexible electronics, sensors, energy devices, and smart materials. However, the fluidity and formability of liquid metals pose significant challenges to their application in fiber structures.

[0005] Fiber materials, characterized by their large specific surface area, high flexibility, and ease of weaving, have attracted widespread attention in wearable electronics, flexible sensors, and smart fabrics. The successful fabrication of liquid metal fibers combines the superior properties of liquid metals with the flexibility of fiber materials, significantly expanding the application scenarios of liquid metals. However, current liquid metal fiber fabrication technologies still face the following challenges:

[0006] (1) The leakage problem caused by high liquidity;

[0007] Liquid metals are in a liquid state at or near room temperature, and their high fluidity makes them extremely prone to leakage during use or processing. Such leakage not only reduces equipment reliability but may also cause environmental safety issues, limiting the widespread adoption of liquid metals in practical applications.

[0008] (2) The packaging process is complex, which affects application efficiency;

[0009] To reduce liquid metal leakage, most current methods employ multi-layer encapsulation structures or external protective materials. However, these methods require additional processing steps, increasing production costs and impacting the flexibility and conductivity of the materials.

[0010] (3) The preparation of fibrous materials is difficult;

[0011] In existing technologies, liquid metals need to be combined with polymer materials to form a stable structure during the fiberization process. However, due to the high fluidity and surface tension of liquid metals, their compatibility with the matrix material is poor, resulting in a complex preparation process and a low yield.

[0012] There are various processes for preparing conductive fibers based on liquid metal materials, such as electrospinning, melt spinning, and hollow fiber injection. For example, patent CN202311681238.0 describes the preparation of liquid metal fiber composite filaments through electrospinning, and further preparation of liquid metal fiber films with interconnected three-dimensional network structures. However, this method cannot prepare single liquid metal fibers, only liquid metal films. Patent CN202110651134.X utilizes injection technology to infuse liquid metal into hollow fibers, using chemical adhesives to enhance the adhesion between the liquid metal and the hollow fibers. However, the hollow fiber injection process is complex and cannot be efficiently and continuously prepared. Patent CN202210012360.8 describes a method for preparing linear liquid metal wires using self-encapsulated organic polymer coatings, employing electrochemical in-situ polymerization. This method requires a large amount of energy from the electrochemical coagulation bath and has certain limitations. The wet-spun sheath-core structure liquid metal fiber of patent CN202410144146.7 focuses on the relationship between the diameter ratio of the circle formed by the liquid metal core layer and the circle formed by the elastic carrier layer. The diameter ratio mainly affects the conductivity and spinnability of the fiber, but does not involve the discussion of the fluidity of the liquid metal. At the same time, under the action of external force, this conductive fiber cannot avoid sensor failure and safety issues caused by liquid metal leakage.

[0013] Therefore, it is of great significance to study a liquid metal fiber based on wet spinning and its preparation method to solve the problems existing in the prior art. Summary of the Invention

[0014] The purpose of this invention is to solve the problems existing in the prior art and to provide a liquid metal fiber based on wet spinning and its preparation method.

[0015] A method for preparing liquid metal fibers involves using a wet spinning process to prepare core-sheath fibers, followed by heat preservation annealing to obtain liquid metal fibers.

[0016] In the core-sheath fiber, the raw material corresponding to the sheath layer is spinning solution I, and the raw material corresponding to the core layer is spinning solution II;

[0017] Spinning solution I is prepared by adding polymer elastomer I to organic solvent I;

[0018] Spinning solution II is prepared by adding liquid metal (LM), solid conductive material and polymer elastomer II to organic solvent II;

[0019] Based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass percentage of solid conductive material is 1-7% and the mass percentage of polymer elastomer II is 5-11%.

[0020] The mass-to-volume ratio of polymer elastomer II to organic solvent II is 200–400 mg: 1 mL.

[0021] As a preferred technical solution:

[0022] The specific steps of the preparation method for the liquid metal fiber described above are as follows:

[0023] (1) Preparation of spinning solution I;

[0024] Add polymer elastomer I to organic solvent I and stir until polymer elastomer I is completely dissolved to obtain spinning solution I;

[0025] (2) Preparation of spinning solution II;

[0026] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, liquid metal and solid conductive material are added to solution A to obtain spinning solution II.

[0027] (3) Liquid metal fibers were prepared by coaxial wet spinning process;

[0028] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound through a winding device to obtain core and sheath fibers. Finally, the core and sheath fibers are placed in a vacuum oven for heat preservation and annealing to obtain liquid metal fibers.

[0029] The feed rate of spinning solution I is 250–400 μm / min, and the feed rate of spinning solution II is 60–150 μm / min; the draw ratio is 1–5:1; the annealing temperature is 50–80℃, and the annealing time is 8–15 h.

[0030] The liquid metal fiber preparation method described above, wherein the liquid metal is one or more of gallium, gallium-indium alloy, and gallium-indium-tin alloy; the solid conductive material is one or more of metallic material and carbon-based material; the metallic material is one or more of silver nanoparticles, copper nanoparticles, silver nanowires, copper nanowires, silver nanosheets, and copper nanosheets; and the carbon-based material is one or more of carbon black, carbon nanotubes, and graphene.

[0031] In the method for preparing liquid metal fiber as described above, polymer elastomer I and polymer elastomer II are each independently selected from one or more of acrylonitrile-butadiene-styrene copolymer (ABS), styrene-ethylene / butene-styrene block copolymer (SEBS), thermoplastic polyurethane (TPU), thermoplastic polyester elastomer (TPPE), thermoplastic silicone elastomer (Geniomer), and styrene-butadiene-styrene block copolymer (SBS).

[0032] In the method for preparing liquid metal fibers as described above, organic solvent I and organic solvent II are each independently selected from one or more of acetone, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAC), and toluene; the coagulation bath is one or more of water, brine, methanol, ethanol, isopropanol, cyclohexane, and hexane; and the brine is a 5 wt% NaCl aqueous solution.

[0033] In the preparation method of liquid metal fiber as described above, the mass ratio of polymer elastomer I to organic solvent I is 15-35:100.

[0034] In the preparation method of liquid metal fiber as described above, the liquid metal needs to be pulverized before being added to solution A. The specific process is as follows: the liquid metal is added to organic solvent III to obtain a mixture, the mixture is ultrasonically treated with an ultrasonic cell pulverizer for 40-80 minutes, then the organic solvent III in the ultrasonically treated mixture is removed by a vacuum filter and the ultrasonically treated liquid metal is retained. The ultrasonically treated liquid metal is placed in a vacuum oven at 100-150°C for 9-15 hours to completely remove the residual organic solvent. Organic solvent III is one or more of acetone, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAC), and toluene.

[0035] The method for preparing liquid metal fibers as described above involves adding liquid metal and solid conductive material to solution A, followed by sequential mixing and defoaming. The mixing time is 90–120 s, and the rotation speed is 2200–2500 r / min. The defoaming time is 90–120 s, and the rotation speed is 2000–2200 r / min. One mixing and one defoaming cycle is defined as one period, and the number of cycles is 5–10.

[0036] The present invention also provides liquid metal fibers prepared by the preparation method described in any of the preceding claims, wherein the liquid metal fibers have a core-sheath structure, the sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material and polymer elastomer II;

[0037] Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not connected to other channels.

[0038] The liquid metal is divided into three parts, referred to as liquid metal I, liquid metal II and liquid metal III respectively; liquid metal I is located in the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network.

[0039] The solid conductive material is divided into three parts, referred to as solid conductive material I, solid conductive material II, and solid conductive material III, respectively. Solid conductive material I is located in the channels of the network structure and is connected to the conductive network. Solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network. Solid conductive material III is located in the channels that are not connected to form a network structure and is not connected to the conductive network.

[0040] Polymer elastomer I and polymer elastomer II exist in the form of solid particles. In the preparation of liquid metal fibers, organic solvents are required to dissolve them. Polymer elastomer I is added to organic solvent I to obtain spinning solution I, and liquid metal, solid conductive material and polymer elastomer II are added to organic solvent II to obtain spinning solution II.

[0041] Spinning solution I was used as the outer spinning solution, and spinning solution II as the inner spinning solution. Both were then added separately to syringes and propelled into a coagulation bath through a coaxial needle. During coagulation, organic solvent I in spinning solution I and organic solvent II in spinning solution II diffused and exchanged with the non-solvents in the coagulation bath. Some of the organic solvent I in spinning solution I and some of the organic solvent II in spinning solution II were displaced, reducing their content and promoting the precipitation of polymer elastomer I and polymer elastomer II to form a solid fiber structure. Subsequent annealing evaporated the organic solvent I, organic solvent II, and non-solvents from the fiber at high temperatures, resulting in a porous fiber interior, with most channels interconnected, forming a polymer elastomer I network and a polymer elastomer II network.

[0042] When polymer elastomer II precipitates to form a polymer elastomer II network, some liquid metal and solid conductive material will be in the interconnected channels. Under the synergistic effect of the solid conductive material and the liquid metal, this part of the liquid metal forms a conductive network. Some liquid metal and solid conductive material will also adhere to the walls of the interconnected channels, while some liquid metal and solid conductive material will be wrapped by polymer elastomer II and will not be connected to the conductive network. The reason why most of the liquid metal and solid conductive material are in the interconnected channels is that in the coagulation bath, polymer elastomer II precipitates and wraps the liquid metal, solid conductive material, solvent and non-solvent. When organic solvent II and non-solvent evaporate in the form of high temperature, the space where the liquid metal, solid conductive material, solvent and non-solvent are located increases, thus forming channels. Some channels are interconnected to form a polymer elastomer II network, while some channels exist alone and are not connected to other channels.

[0043] The annealing process in the preparation method can also shrink and solidify the polymer elastomer I network and the polymer elastomer II network.

[0044] As a preferred technical solution:

[0045] As described above, the liquid metal fiber has a breaking tensile rate of 1653–1876%, a tensile strength of 5.7–12.9 N, no liquid metal leakage was observed when stretched to 150%, an elastic recovery rate of 86–97% when stretched to 150%, a strain resistance stability of 47–96% when stretched to 150%, and a strain resistance cyclic stability of 2.57–6.13% when stretched to 100%.

[0046] Invention principle:

[0047] Liquid metals possess low viscosity and high surface tension, existing in a liquid state and readily flowing and diffusing under external forces. This high fluidity is the primary cause of leakage problems in existing liquid metal fibers. Furthermore, although the liquid metal in existing liquid metal fibers exhibits good electrical conductivity, its high fluidity leads to conductivity instability. This instability refers to the fact that while the liquid metal's high fluidity results in good conductivity at one point, other areas with less liquid metal exhibit poor conductivity.

[0048] The liquid metal fiber prepared by this invention is a core-sheath fiber. The sheath layer of the core-sheath fiber is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. After mixing with liquid metal, polymer elastomer II can significantly increase the overall viscosity and adhesion of the system and slow down the flow of liquid metal. Furthermore, during the mixing process, polymer elastomer II can form a certain degree of physical coating or network structure with liquid metal. This structure can restrict the free flow of liquid metal, making the liquid metal more stable in the fiber.

[0049] Adjusting the proportion of polymer elastomer II in the core spinning solution can control the flowability of the spinning solution. Increasing the proportion of polymer elastomer II in the spinning solution can further increase the viscosity of the mixture, thereby enhancing the ability to control the flowability of liquid metal.

[0050] Since the conductivity of liquid metal mainly depends on its continuity, if the liquid metal is dispersed into non-conductive isolated regions, the overall conductivity of the material will be significantly reduced. During the preparation of spinning solution II, the liquid metal exists in the form of tiny droplets or a dispersed phase. If the proportion of polymer elastomer II is high, polymer elastomer II will encapsulate the liquid metal to form a composite phase, preventing the liquid metal in the liquid metal fiber core layer from being uniformly distributed within polymer elastomer II and thus failing to form a conductive network structure. Furthermore, the high surface tension of liquid metal makes it prone to forming isolated spheres or droplets in the polymer matrix, which also prevents the liquid metal from effectively connecting to form a conductive network.

[0051] The addition of polymer elastomer II to spinning solution II solves the leakage problem caused by the high flow of liquid metal, and also solves the problem of unstable conductivity. Although the conductivity is not significantly reduced within the range of the addition amount of the present invention, the conductivity is still reduced compared with that without the addition of polymer elastomer II.

[0052] Adding solid conductive materials to polymers can increase conductivity. However, in the prior art, when solid conductive materials are added to polymers, the contact points between the solid conductive materials may separate during polymer stretching or bending, leading to interruption of the conductive path and thus causing instability in conductivity. Therefore, those skilled in the art would also recognize that, under stretching conditions, incorporating solid conductive materials into the polymer elastomer II of the present invention cannot improve the conductivity of the liquid metal fibers.

[0053] However, experiments in this invention have revealed a synergistic effect between liquid metal and solid conductive material. Under stretching conditions, incorporating solid conductive material into the polymer elastomer II of this invention can further prevent leakage of liquid metal from the fiber while improving the conductivity of the liquid metal fiber, achieving unexpected technical effects. The specific analysis is as follows:

[0054] Due to their solid state, solid conductive materials in polymer elastomer II can only provide preliminary conductive pathways in the microstructure when added in small amounts. During stretching, the spacing between solid conductive materials increases in existing technologies, leading to a decrease in conductivity. However, in the technical solution of this invention, solid conductive materials can be adsorbed onto the surface of liquid metal, altering the surface energy distribution of the liquid metal, reducing surface tension, and making it easier for the liquid metal to disperse in the polymer matrix, reducing the formation of small spheres or droplets. The solid conductive materials distributed on the surface or interface of the liquid metal form a structure similar to a physical barrier. This barrier restricts the liquid metal particles from further shrinking into spheres, helping to extend their shape or maintain an irregular morphology, allowing the liquid metal to effectively connect and form a conductive network, significantly improving conductivity.

[0055] In addition, adding solid conductive materials to liquid metal can further reduce the fluidity of liquid metal, which can better fix the liquid metal in the initial position and thus avoid leakage; the initial position refers to the initial distribution position of liquid metal in polymer elastomer II, which is generally the region formed during the preparation process.

[0056] Liquid metal exhibits excellent "dynamic adaptation" during stretching. When liquid metal fibers are subjected to external forces, the liquid metal can adjust its distribution within the fiber core, reducing the damage to the fiber's conductivity and enabling spontaneous repair of micro-damage to the core caused by external forces, thus ensuring the material's long-term stability. Specifically, the liquid metal is confined within core channels formed by polymer elastomers. These channels provide a restricted and controlled distribution space for the liquid metal. When the fiber is stretched, the cross-sectional area of ​​the core channels shrinks, further compressing the liquid metal's position, limiting its flow range, making the fiber more stable, and reducing the risk of leakage. Furthermore, due to the fluidity of the liquid metal, when the core breaks or develops voids during fiber stretching, the liquid metal redistributes to the damaged area, filling cracks or gaps and achieving self-repair. As the external force is released, the liquid metal returns to its initial position under the influence of surface tension (solid conductive materials only reduce the tension of the liquid metal, not completely eliminate it), restoring its original distribution state. This dynamic adjustment mechanism effectively enhances the mechanical and electrical properties of the material, ensuring its stability and reliability under complex load conditions.

[0057] In the wet spinning process, the spinning solution rapidly solidifies into fibers via a coagulation bath. The continuous phase formed by the polymer elastomer I in the sheath during coagulation effectively coats the core layer, further reducing the risk of liquid metal leakage. Furthermore, the fiber structure formed after spinning confines the liquid metal within the continuous fiber core layer at the microscale, providing a natural encapsulation effect. This encapsulation avoids additional sealing processes, making the fibers lighter and more flexible.

[0058] By controlling the doping ratio of liquid metal to solid conductive material in the core layer, a balance can be achieved between the tensile strength, conductivity, and leakage potential of the liquid metal fiber. In the technical solution of this invention, the total mass of liquid metal, solid conductive material, and polymer elastomer II is used as a basis. The mass percentage of solid conductive material is 1-7%, and the mass percentage of polymer elastomer II is 5-11%. When the content of polymer elastomer II is higher than the defined range, the fiber conductivity will be poor. When the content of polymer elastomer II is lower than the defined range, the spinnability of the fiber core layer will be challenged. When the liquid metal content is higher than the defined range, the liquid metal in the fiber core layer is too fluid, which can easily cause leakage. When the liquid metal content is lower than the defined range, the conductive network in the core layer breaks when the fiber is stretched, and the liquid metal cannot be redistributed in time, resulting in damage to the conductivity of the fiber. When the content of solid conductive material is higher than the defined range, it is easy to agglomerate in polymer elastomer II, forming isolated particle clusters, and the flexibility and elasticity of the fiber will decrease significantly. When the content of solid conductive material is lower than the defined range, the increase in the conductivity of the fiber is not significant. Specifically, in the prior art, when solid conductive materials are added to polymer elastomers, these materials tend to agglomerate, forming isolated particle clusters instead of being uniformly distributed in the matrix. This prevents the formation of a continuous conductive network between the particles, thus affecting the overall conductivity. The present invention solves this problem by utilizing the fluidity of liquid metal within the specified addition range to uniformly disperse the solid conductive materials, thereby preventing the formation of isolated particle clusters.

[0059] Beneficial effects:

[0060] (1) A liquid metal fiber based on wet spinning of the present invention has excellent stretch-recovery stability and stretch-conductivity stability. The fiber can maintain the stability of its shape and properties during repeated stretching and relaxation, while its conductivity is not significantly affected by mechanical deformation.

[0061] (2) The present invention provides a liquid metal fiber based on wet spinning, which has no liquid metal leakage and is safe and reliable: through unique design and process, the fluidity of liquid metal is controlled and the liquid metal is always effectively covered, avoiding leakage risk and improving the safety and environmental adaptability of the material;

[0062] (3) The present invention provides a method for preparing liquid metal fibers based on wet spinning, which has excellent spinnability and can be prepared continuously: wet spinning realizes the high compatibility between liquid metal and matrix material, supports a stable process, and has high yield and process scalability.

[0063] (4) The present invention provides a method for preparing liquid metal fibers, which solves the technical problem that a single component cannot simultaneously meet the requirements of conductivity and tensile properties by simultaneously adding liquid metal and solid conductive material to the spinning solution of the functional conductive core layer. If only liquid metal is added, the conductivity will be unstable due to its high fluidity, and if only solid conductive material is added, the tensile conductivity requirements cannot be met. However, by mixing liquid metal and solid conductive material in a reasonable ratio, both conductivity and tensile properties can be achieved, and liquid metal leakage can be effectively prevented. This provides important technical support and innovative ideas for the application of liquid metal in flexible electronic devices. Attached Figure Description

[0064] Figure 1 This is a schematic diagram of the cross-section of a liquid metal fiber obtained by wet spinning according to the present invention;

[0065] Figure 2 This is a schematic diagram illustrating the concept of a liquid metal fiber based on wet spinning obtained by the present invention.

[0066] Figure 3 This is a conceptual diagram of the core layer cross-section of a liquid metal fiber based on wet spinning obtained in this invention;

[0067] Figure 4 The graph shows a comparison of the electrical stability of fibers a, b, c, and d under different strains; where fiber c is the liquid metal fiber prepared in Example 1; the difference between fibers a, b, and d and fiber c is that the contents of polymer elastomer II and liquid metal are different while the core layer mass remains unchanged.

[0068] Figure 5 This is a conductivity stability diagram of a liquid metal fiber based on wet spinning obtained in Embodiment 1 of the present invention connected to an LED lamp series circuit.

[0069] Figure 6 The image shows a scanning electron microscope (SEM) image of a liquid metal fiber based on wet spinning obtained in Example 2 of the present invention after stretching recovery; wherein, (a) is a surface image of the fiber sheath layer, and (b) is a magnified partial surface image of the fiber sheath layer.

[0070] Figure 7 This is a scanning electron microscope (SEM) cross-sectional image of a liquid metal fiber based on wet spinning obtained in Example 3 of the present invention after stretching recovery; wherein, (c) is a cross-sectional image of the fiber after stretching recovery, and (d) is a magnified cross-sectional image of the core layer after stretching recovery;

[0071] Among them, 1-sheath layer, 2-core layer, 3-liquid metal, 4-solid conductive material, 5-polymer elastomer II. Detailed Implementation

[0072] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0073] The testing standards / methods used in this invention are as follows:

[0074] Tensile strength at break and tensile strength: The tensile strength at break and tensile strength of the fiber were tested at room temperature using an Instron 5965 universal testing machine at a tensile speed of 50 mm / min.

[0075] Elastic recovery rate at 150% stretch: The elastic recovery performance of the fiber was tested using a multifilament spandex elasticity tester. The stretching speed was 400 mm / min, the load application time was 30 s, the deformation recovery time after unloading was 30 s, and the elastic recovery performance was tested at a strain of 150%.

[0076] Leakage characterization: The surface and cross-section of the liquid metal fiber were observed using an S-4800 scanning electron microscope to check for leakage and overflow of liquid metal. The voltage of the SEM used was 5kV.

[0077] Strain resistance stability at 150% stretch: Under room temperature conditions, the strain resistance stability of liquid metal fiber was tested using a transverse tensile testing machine and a DMM6500 digital multimeter. The strain was fixed at 150% and the stretching frequency was 1000Hz. The strain resistance stability was expressed as ΔR / R0, where ΔR is the change in resistance before and after stretching, and R0 is the original resistance value before stretching.

[0078] Cyclic stability of strain gauge at 100% tension: Under room temperature conditions, the cyclic stability of liquid metal fibers was tested using a transverse tensile testing machine and a DMM6500 digital multimeter. The strain was kept constant at 100%, and the cycle was 50 times at a tensile frequency of 1000 Hz. The cyclic stability of strain gauge is expressed as drift rate, which is calculated as: Drift rate = (resistance after the 50th cycle - initial resistance) / initial resistance * 100%. The initial resistance refers to the resistance before tensile testing.

[0079] The sources of some of the materials in this invention are as follows:

[0080] SEBS: Manufacturer: Shanghai Susheng Plastics Co., Ltd., Grade: G1701.

[0081] TPU: Manufacturer: Covestro Polymers Ltd., Grade: 385S.

[0082] TPPE: Manufacturer: Dongguan Fengda Plastic Raw Materials Co., Ltd., Grade: 4556.

[0083] Thermoplastic silicone elastomer: Manufacturer: Dongguan Hongtu Plastic Raw Materials Co., Ltd., Grade: 9107.

[0084] SBS: Manufacturer: Jinan Xinhaoyuan Chemical Co., Ltd., Grade: 1002.

[0085] In this embodiment of the invention, when the liquid metal used is a gallium-indium alloy, the content of gallium is 75.5 wt% and the content of indium is 24.5 wt%; when the liquid metal is a gallium-indium-tin alloy, the content of gallium is 68.5 wt%, the content of indium is 21.5 wt%, and the content of tin is 10 wt%.

[0086] Example 1

[0087] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0088] (1) Preparation of raw materials:

[0089] Polymer elastomer I: TPU;

[0090] Organic solvent I: DMF;

[0091] Organic Solvent III: DMF;

[0092] Polymer Elastomer II: TPU;

[0093] Organic Solvent II: DMF;

[0094] Liquid metal: gallium-indium alloy;

[0095] Solid conductive material: copper nanoparticles with a particle size of 1 μm;

[0096] Coagulation bath: water and ethanol in a volume ratio of 5:1;

[0097] (2) Preparation of spinning solution I;

[0098] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100.

[0099] (3) Pulverization of liquid metal;

[0100] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0101] (4) Preparation of spinning solution II;

[0102] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0103] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 5% of the mass and polymer elastomer II accounting for 9% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 300 mg: 1 mL. The mixing and stirring time was 100 s, and the rotation speed was 2300 r / min. The defoaming time was 100 s, and the rotation speed was 2100 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 8.

[0104] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0105] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0106] The feed rate of spinning solution I is 300 μm / min, and the feed rate of spinning solution II is 60 μm / min; the draw ratio is 2:1; the annealing temperature is 60℃, and the annealing time is 12h.

[0107] like Figures 1-3As shown, the final liquid metal fiber has a core-sheath structure. Sheath 1 is composed of polymer elastomer I, and core 2 is composed of liquid metal 3, solid conductive material 4, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not connected to other channels. Liquid metal 3 is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. Solid conductive material 4 is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0108] The breaking tensile strength of the liquid metal fiber is 1653%, the tensile strength is 10.4 N, no liquid metal leakage was observed when stretched to 150%, the elastic recovery rate is 93% when stretched to 150%, the strain resistance stability is 81% when stretched to 150%, and the strain resistance cyclic stability is 4.26% when stretched to 100%.

[0109] like Figure 5 As shown, the resistance change is approximately 10Ω from the initial strain to 100% strain, demonstrating the stability of the fiber's strain resistance. When the fiber is cyclically stretched at 100% strain, the resistance change is found to be basically stable, indicating that the strain resistance of the liquid metal fiber has good cyclic stability.

[0110] like Figure 4As shown, based on Example 1, the influence of different contents of polymer elastomer II in the core layer on the strain resistance stability of the fiber was investigated. The overall mass of the core layer remained constant, while the mass of the solid conductive material in the core layer remained constant when the content of polymer elastomer II changed, while the mass of the liquid metal was adjusted accordingly with the mass of polymer elastomer II. Fiber a was designated as having a polymer elastomer II content of 5 wt%; fiber b as having a content of 7 wt%; fiber c (i.e., the liquid metal fiber of Example 1) as having a content of 9 wt%; and fiber d as having a content of 11 wt%. The resistance stability of fibers a, b, c, and d was compared under different strains. At a strain of 50%, fiber b exhibited the smallest resistance change rate and the best stability. Differences appeared at strains of 100–200%, with the liquid metal fiber of Example 1 showing a smaller resistance change rate. Therefore, in overall comparison, fibers at concentrations of 7 wt% and 9 wt% exhibit better stability. Fiber a shows a large rate of resistance change under different strains, possibly because the high content of liquid metal in the core layer causes the conductive circuit cross-section to essentially fit the inner edge of the sheath layer. During stretching, the smaller fiber cross-section significantly impacts the cross-section of the core layer pathway, resulting in a large rate of resistance change. Fiber d has the lowest liquid metal content, and its large rate of resistance change due to strain is likely caused by the low liquid metal content in the core layer, leading to unstable pathways.

[0111] Example 2

[0112] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0113] (1) Preparation of raw materials:

[0114] Polymer elastomer I: TPU;

[0115] Organic solvent I: toluene and isopropanol in a volume ratio of 7:3;

[0116] Organic Solvent III: Toluene and isopropanol in a volume ratio of 7:3;

[0117] Polymer Elastomer II: TPU;

[0118] Organic Solvent II: Toluene and isopropanol in a volume ratio of 7:3;

[0119] Liquid metal: gallium-indium alloy;

[0120] Solid conductive material: copper nanowires, 20 nm in diameter and 2 μm in length;

[0121] Coagulation bath: water and ethanol in a volume ratio of 5:1;

[0122] (2) Preparation of spinning solution I;

[0123] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100.

[0124] (3) Pulverization of liquid metal;

[0125] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0126] (4) Preparation of spinning solution II;

[0127] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0128] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 7% of the mass and polymer elastomer II accounting for 7% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 200 mg: 1 mL. The mixing and stirring time was 90 s, and the rotation speed was 2200 r / min. The defoaming time was 90 s, and the rotation speed was 2000 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 5.

[0129] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0130] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0131] The feed rate of spinning solution I is 400 μm / min, and the feed rate of spinning solution II is 150 μm / min; the draw ratio is 5:1; the annealing temperature is 80℃, and the annealing time is 8h.

[0132] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0133] The breaking tensile strength of the liquid metal fiber is 1703%, the tensile strength is 5.7N, no liquid metal leakage was observed when stretched to 150%, the elastic recovery rate is 86% when stretched to 150%, the strain resistance stability is 57% when stretched to 150%, and the strain resistance cyclic stability is 2.78% when stretched to 100%.

[0134] like Figure 6 As shown, the fiber surface has a closed groove structure, and the surface structure is uniform and seamless, with no tendency for liquid metal leakage, proving the integrity of the sheath core structure.

[0135] Example 3

[0136] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0137] (1) Preparation of raw materials:

[0138] Polymer elastomer I: TPU;

[0139] Organic solvent I: DMSO;

[0140] Organic Solvent III: DMSO;

[0141] Polymer elastomer II: SEBS;

[0142] Organic Solvent II: DMSO;

[0143] Liquid metal: gallium-indium alloy;

[0144] Solid conductive material: silver nanoparticles with a particle size of 1 μm;

[0145] Coagulation bath: water and ethanol in a volume ratio of 5:1;

[0146] (2) Preparation of spinning solution I;

[0147] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 35:100.

[0148] (3) Pulverization of liquid metal;

[0149] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0150] (4) Preparation of spinning solution II;

[0151] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0152] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 1% of the mass and polymer elastomer II accounting for 9% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 400 mg: 1 mL. The mixing and stirring time was 120 s, and the rotation speed was 2500 r / min. The defoaming time was 120 s, and the rotation speed was 2200 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 10.

[0153] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0154] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0155] The feed rate of spinning solution I is 250 μm / min, and the feed rate of spinning solution II is 100 μm / min; the draw ratio is 1:1; the annealing temperature is 50℃, and the annealing time is 15h.

[0156] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0157] The breaking tensile strength of the liquid metal fiber is 1876%, the tensile strength is 12.9 N, no liquid metal leakage was observed when stretched to 150%, the elastic recovery rate is 96% when stretched to 150%, the strain resistance stability is 96% when stretched to 150%, and the strain resistance cyclic stability is 6.13% when stretched to 100%.

[0158] In such Figure 7 The cross-sectional view shown in (c) shows that the core layer is completely enclosed by the sheath layer, with no leakage; in the cross-sectional view shown in (c)... Figure 7 In the magnified view shown in (d), dispersed liquid metal 3 is visible, encapsulated by polymer elastomer II 5, with some surfaces having solid conductive material 4 attached. This demonstrates that the sheath-core structure and core layer doping can effectively improve the fluidity of the liquid metal, thereby reducing the possibility of liquid metal leakage.

[0159] Example 4

[0160] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0161] (1) Preparation of raw materials:

[0162] Polymer elastomer I: SEBS;

[0163] Organic solvent I: Toluene;

[0164] Organic solvent III: Toluene;

[0165] Polymer elastomer II: SEBS;

[0166] Organic solvent II: Toluene;

[0167] Liquid metal: gallium-indium alloy;

[0168] Solid conductive material: carbon nanotubes, 2 nm in diameter and 5 μm in length;

[0169] Coagulation bath: water and isopropanol in a volume ratio of 5:1;

[0170] (2) Preparation of spinning solution I;

[0171] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100.

[0172] (3) Pulverization of liquid metal;

[0173] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0174] (4) Preparation of spinning solution II;

[0175] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0176] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 3% of the mass and polymer elastomer II accounting for 11% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 300 mg: 1 mL. The mixing and stirring time was 110 s, and the rotation speed was 2200 r / min. The defoaming time was 110 s, and the rotation speed was 2000 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one period, and the number of periods was 7.

[0177] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0178] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0179] The feed rate of spinning solution I is 300 μm / min, and the feed rate of spinning solution II is 120 μm / min; the draw ratio is 3:1; the annealing temperature is 60℃, and the annealing time is 10h.

[0180] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0181] The breaking tensile rate of the liquid metal fiber is 1849%, the tensile strength is 8.3N, no liquid metal leakage occurs when stretched to 150%, the elastic recovery rate is 97% when stretched to 150%, the strain resistance stability is 47% when stretched to 150%, and the strain resistance cyclic stability is 2.57% when stretched to 100%.

[0182] Example 5

[0183] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0184] (1) Preparation of raw materials:

[0185] Polymer elastomer I: SBS;

[0186] Organic solvent I: Toluene and THF in a volume ratio of 6:4;

[0187] Organic solvent III: Acetone;

[0188] Polymer Elastomer II: Thermoplastic Silicone Elastomer;

[0189] Organic Solvent II: Toluene and THF in a volume ratio of 6:4;

[0190] Liquid metal: gallium;

[0191] Solid conductive material: silver nanosheets, 20 nm thick, 3 μm lateral dimension;

[0192] Coagulation bath: cyclohexane and brine in a 1:1 volume ratio, the brine being a 5 wt% NaCl aqueous solution;

[0193] (2) Preparation of spinning solution I;

[0194] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 20:100.

[0195] (3) Pulverization of liquid metal;

[0196] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0197] (4) Preparation of spinning solution II;

[0198] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0199] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 5% of the mass and polymer elastomer II accounting for 8% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 250 mg: 1 mL. The mixing and stirring time was 110 s, and the rotation speed was 2400 r / min. The defoaming time was 110 s, and the rotation speed was 2200 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 9.

[0200] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0201] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0202] The feed rate of spinning solution I was 350 μm / min, and the feed rate of spinning solution II was 70 μm / min; the draw ratio was 4:1; the annealing temperature was 70℃, and the annealing time was 11h.

[0203] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0204] The breaking tensile strength of the liquid metal fiber is 1750%, the tensile strength is 9.5N, no liquid metal leakage occurs when stretched to 150%, the elastic recovery rate is 90% when stretched to 150%, the strain resistance stability is 65% when stretched to 150%, and the strain resistance cyclic stability is 3.80% when stretched to 100%.

[0205] Example 6

[0206] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0207] (1) Preparation of raw materials:

[0208] Polymer elastomer I: TPPE;

[0209] Organic solvent I: DMAC;

[0210] Organic Solvent III: DMAC;

[0211] Polymer Elastomer II: TPU;

[0212] Organic Solvent II: DMAC;

[0213] Liquid metal: Gallium indium tin alloy;

[0214] Solid conductive material: copper nanosheets, 20 nm thick, 3 μm lateral dimension;

[0215] Coagulation bath: water and methanol in a volume ratio of 5:1;

[0216] (2) Preparation of spinning solution I;

[0217] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 30:100.

[0218] (3) Pulverization of liquid metal;

[0219] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0220] (4) Preparation of spinning solution II;

[0221] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0222] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 6% of the mass and polymer elastomer II accounting for 6% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 350 mg: 1 mL. The mixing and stirring time was 100 s, and the rotation speed was 2200 r / min. The defoaming time was 100 s, and the rotation speed was 2000 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 6.

[0223] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0224] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0225] The feed rate of spinning solution I was 320 μm / min, and the feed rate of spinning solution II was 130 μm / min; the draw ratio was 2:1; the annealing temperature was 60℃, and the annealing time was 12h.

[0226] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0227] The breaking tensile strength of the liquid metal fiber is 1685%, the tensile strength is 11.7 N, no liquid metal leakage was observed when stretched to 150%, the elastic recovery rate is 92% when stretched to 150%, the strain resistance stability is 78% when stretched to 150%, and the strain resistance cyclic stability is 4.02% when stretched to 100%.

[0228] Example 7

[0229] A method for preparing liquid metal fibers, the specific steps of which are as follows:

[0230] (1) Preparation of raw materials:

[0231] Polymer elastomer I: Thermoplastic silicone elastomer;

[0232] Organic solvent I: THF;

[0233] Organic solvent III: Acetone;

[0234] Polymer elastomer II: SEBS;

[0235] Organic solvent II: THF;

[0236] Liquid metal: Gallium-indium alloy;

[0237] Solid conductive material: copper nanoparticles with a particle size of 1 μm;

[0238] Coagulation bath: cyclohexane and hexane in a volume ratio of 3:2;

[0239] (2) Preparation of spinning solution I;

[0240] Polymer elastomer I is added to organic solvent I and stirred until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100.

[0241] (3) Pulverization of liquid metal;

[0242] Liquid metal was added to organic solvent III to obtain a mixture. The mixture was ultrasonically treated with an ultrasonic cell disruptor for 60 min. Then, organic solvent III was removed from the ultrasonically treated mixture, and the ultrasonically treated liquid metal was retained. The ultrasonically treated liquid metal was placed in a vacuum oven at 120°C for 12 h. The mass-to-volume ratio of liquid metal to organic solvent III was 100 mg: 1 mL.

[0243] (4) Preparation of spinning solution II;

[0244] Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, pulverized liquid metal and solid conductive material are added to solution A, and then mixed and stirred and defoamed in sequence to obtain spinning solution II.

[0245] The total mass of liquid metal, solid conductive material, and polymer elastomer II was used as the baseline, with the solid conductive material accounting for 4% of the mass and polymer elastomer II accounting for 7% of the mass. The mass-to-volume ratio of polymer elastomer II to organic solvent II was 320 mg: 1 mL. The mixing and stirring time was 120 s, and the rotation speed was 2300 r / min. The defoaming time was 120 s, and the rotation speed was 2100 r / min. One mixing and stirring cycle and one defoaming and stirring cycle were counted as one cycle, and the number of cycles was 8.

[0246] (5) Liquid metal fibers were prepared by coaxial wet spinning process;

[0247] Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-annealed to obtain liquid metal fibers.

[0248] The feed rate of spinning solution I is 380 μm / min, and the feed rate of spinning solution II is 90 μm / min; the draw ratio is 3:1; the annealing temperature is 80℃, and the annealing time is 9h.

[0249] The final liquid metal fiber has a core-sheath structure. The sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not interconnected with other channels. The liquid metal is divided into three parts, denoted as liquid metal I, liquid metal II, and liquid metal III. Liquid metal I is located within the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, denoted as solid conductive material I, solid conductive material II, and solid conductive material III. Solid conductive material I is located within the channels of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and solid conductive material III is located in the unconnected channels that do not form a network structure and is not connected to the conductive network.

[0250] The breaking tensile rate of the liquid metal fiber is 1762%, the tensile strength is 10.1 N, no liquid metal leakage was observed when stretched to 150%, the elastic recovery rate is 94% when stretched to 150%, the strain resistance stability is 71% when stretched to 150%, and the strain resistance cyclic stability is 3.68% when stretched to 100%.

Claims

1. A liquid metal fiber, characterized in that, Liquid metal fibers have a core-sheath structure. The sheath is composed of polymer elastomer I, and the core is composed of liquid metal, solid conductive material, and polymer elastomer II. Polymer elastomer II has multiple channels, some of which are interconnected to form a network structure, while the remaining channels are not connected to other channels. The liquid metal is divided into three parts, referred to as liquid metal I, liquid metal II and liquid metal III respectively; liquid metal I is located in the channels of the network structure to form a conductive network, liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network. The solid conductive material is divided into three parts, referred to as solid conductive material I, solid conductive material II and solid conductive material III respectively. Solid conductive material I is located in the pores of the network structure and is connected to the conductive network. Solid conductive material II is located on the pore wall of the pores in the network structure and is connected to the conductive network. Solid conductive material III is located in the pores that are not connected to form a network structure and is not connected to the conductive network. Based on the total mass of liquid metal, solid conductive material, and polymer elastomer II, the mass percentage of solid conductive material is 1-7%, and the mass percentage of polymer elastomer II is 5-11%. The breaking tensile strength of the liquid metal fiber is 1653~1876%, the tensile strength is 5.7~12.9N, no liquid metal leakage occurred when stretched by 150%, and the elastic recovery rate is 86~97% when stretched by 150%.

2. The method for preparing liquid metal fiber according to claim 1, characterized in that, Core-sheath fibers were prepared by wet spinning process and then obtained as liquid metal fibers after heat preservation annealing. In the core-sheath fiber, the raw material corresponding to the sheath layer is spinning solution I, and the raw material corresponding to the core layer is spinning solution II; Spinning solution I is prepared by adding polymer elastomer I to organic solvent I; Spinning solution II is prepared by adding liquid metal, solid conductive material and polymer elastomer II to organic solvent II; The mass-to-volume ratio of polymer elastomer II to organic solvent II is 200~400 mg: 1 mL; The strain resistance stability of the prepared liquid metal fiber is 47~96% when stretched by 150%, and the strain resistance cyclic stability is 2.57~6.13% when stretched by 100%.

3. The method for preparing liquid metal fiber according to claim 2, characterized in that, The specific steps of the preparation method are as follows: (1) Preparation of spinning solution I; Add polymer elastomer I to organic solvent I and stir until polymer elastomer I is completely dissolved to obtain spinning solution I; (2) Preparation of spinning solution II; Polymer elastomer II is added to organic solvent II and stirred until polymer elastomer II is completely dissolved to obtain solution A. Then, liquid metal and solid conductive material are added to solution A to obtain spinning solution II. (3) Liquid metal fibers were prepared by coaxial wet spinning process; Spinning solution I is used as the outer spinning solution and spinning solution II is used as the inner spinning solution. Then, both are added into a syringe and spinning solution I and spinning solution II are pushed into the coagulation bath through a coaxial needle to obtain nascent fibers. The nascent fibers are then drawn and wound to obtain core-sheath fibers. Finally, the core-sheath fibers are heat-preserved and annealed to obtain liquid metal fibers. The feed rate of spinning solution I is 250~400μm / min, and the feed rate of spinning solution II is 60~150μm / min; the draw ratio is 1~5:1; the annealing temperature is 50~80℃, and the annealing time is 8~15h.

4. The method for preparing liquid metal fiber according to claim 3, characterized in that, The liquid metal is one or more of gallium, gallium-indium alloy, and gallium-indium-tin alloy; the solid conductive material is one or more of metallic materials and carbon-based materials; the metallic material is one or more of silver nanoparticles, copper nanoparticles, silver nanowires, copper nanowires, silver nanosheets, and copper nanosheets; and the carbon-based material is one or more of carbon black, carbon nanotubes, and graphene.

5. The method for preparing liquid metal fiber according to claim 4, characterized in that, Polymer elastomer I and polymer elastomer II are each independently selected from one or more of acrylonitrile-butadiene-styrene copolymers, styrene-ethylene / butene-styrene block copolymers, thermoplastic polyurethanes, thermoplastic polyester elastomers, thermoplastic silicone elastomers, and styrene-butadiene-styrene block copolymers.

6. The method for preparing liquid metal fiber according to claim 5, characterized in that, Organic solvent I and organic solvent II are each independently selected from one or more of acetone, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and toluene; the coagulation bath is one or more of water, brine, methanol, ethanol, isopropanol, cyclohexane and hexane; the brine is a 5 wt% NaCl aqueous solution.

7. The method for preparing liquid metal fiber according to claim 6, characterized in that, The mass ratio of polymer elastomer I to organic solvent I is 15~35:

100.

8. The method for preparing liquid metal fiber according to claim 7, characterized in that, Before adding the liquid metal to solution A, it needs to be pulverized. The specific process is as follows: add the liquid metal to organic solvent III to obtain a mixture, sonicate the mixture with an ultrasonic cell disruptor for 40-80 minutes, then remove organic solvent III from the ultrasonic mixture and retain the ultrasonic liquid metal, and place the ultrasonic liquid metal in a vacuum oven at 100-150°C for 9-15 hours; organic solvent III is one or more of acetone, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and toluene.

9. The method for preparing liquid metal fiber according to claim 8, characterized in that, After adding liquid metal and solid conductive material to solution A, mixing and defoaming are performed sequentially. The mixing time is 90~120s and the rotation speed is 2200~2500r / min. The defoaming time is 90~120s and the rotation speed is 2000~2200r / min. One mixing and one defoaming is recorded as one cycle, and the number of cycles is 5~10.

Citation Information

Patent Citations

  • Liquid metal fiber and preparation method and application thereof

    CN115464122A

  • Preparation method and application of self-packaging organic polymer coated liquid metal wire

    CN116453774A

  • Fiber velometer made of liquid metal sensing fiber and application of fiber velometer in intelligent elastic band

    CN118007279A

  • Electrostatic spinning-based liquid metal composite filament, fiber film, flexible electronic composite material and preparation method thereof

    CN117702302A

  • Elastic conductive fiber, elastic conductive fiber with self-enhanced electrical properties at high and low temperatures, and preparation method and application of elastic conductive fiber

    CN118109921A